Exploring Positive Education Principles in English Language Instruction within Teacher Education Programs - Ummul Ma rufa , Ika Meilinda (Linguapedia, 2025)
The concept of positive education has gained considerable attention in global educational discourse, its practical application within teacher training programs particularly in English education departments remains underexplored. This study aim explores the implementation of positive education principle within English teacher education program. The qualitative research approach is used by employing semi-structured interviews to facilitates an in-depth exploration of participants' experiences and perceptions regarding the implementation of positive education principles. A purposive sampling technique was used to select participants who have relevant experiences and are willing to provide rich insights. Data were analyzed using thematic analysis. The findings illustrate that the implementation of positive education in the English education program contributes significantly to both the academic and emotional development of students.